An architecture as a code framework to manage documentation of IT projects - Christophe Gaie; Bertrand Florat; Steven Morvan (Applied Computing and Informatics, 2025)
Purpose – In the present article, the authors tackle the problem of IT documentation, which plays an important role in information technology (IT) project management. Design/methodology/approach – They provide a simple tool based on five complementary views, which should be detailed by the project team using a classic source code management platform. Findings – The proposed tool is open source and may be reused by any IT team in various project contexts and heterogeneous development methods. Originality/value – This research provides an operational framework, which facilitates IT project management and documentation. The framework is open source and may be easily downloaded by any other IT team.